2015
DOI: 10.5301/jva.5000363
|View full text |Cite
|
Sign up to set email alerts
|

Alternative Venous Outflow by Brachial to Jugular Vein Vascular Access for Hemodialysis in the Exhausted Upper Extremities

Abstract: A brachial-jugular AV graft showed satisfactory results in terms of patency and complication rate. The IJV could be a good outflow vein for an AV fistula if the IJV is preserved in patients with chronic renal failure who have subclavian or axillary vein stenosis or occlusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
(29 reference statements)
0
0
0
Order By: Relevance
“…The external jugular vein was identified as a viable outflow conduit for arteriovenous fistulas of the upper extremity in cases where the axillary veins are occluded, exhibiting acceptable patency rates (9). In another study, the use of an ipsilateral internal jugular vein (IJV) as an AV outflow vein was examined in patients with subclavian or axillary vein stenosis or occlusion (10). The results indicated that a brachialjugular AV graft may achieve satisfactory results in terms of patency and complication rate, although the primary patency rate decreases significantly over time.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The external jugular vein was identified as a viable outflow conduit for arteriovenous fistulas of the upper extremity in cases where the axillary veins are occluded, exhibiting acceptable patency rates (9). In another study, the use of an ipsilateral internal jugular vein (IJV) as an AV outflow vein was examined in patients with subclavian or axillary vein stenosis or occlusion (10). The results indicated that a brachialjugular AV graft may achieve satisfactory results in terms of patency and complication rate, although the primary patency rate decreases significantly over time.…”
Section: Introductionmentioning
confidence: 99%
“…The results indicated that a brachialjugular AV graft may achieve satisfactory results in terms of patency and complication rate, although the primary patency rate decreases significantly over time. The use of the IJV as an outflow vein should be the last option for using a particular arm due to the risk of complications such as steal syndrome, seroma, hematoma, swollen arm, infections, pseudoaneurysm, bleeding from puncture site, stenosis and thrombosis (10). In the present case, a prosthetic AV loop between the brachial artery (BA) and the EJV was used for a patient whose vascular conditions did not allow for the creation of another type of upper limb access.…”
Section: Introductionmentioning
confidence: 99%